Deciphering core proteins of osteoporosis with iron accumulation by proteomics in human bone - Wang, Aifei; Zhang, Hui; Li, Guangfei; Chen, Bin; Li, Junjie; Zhang, Tao; Liu, Baoshan; Cao, Zihou; Liu, Gongwen; Jia, Peng; Xu, Youjia (Frontiers in Endocrinology, 2022)
Iron accumulation is an independent risk factor for postmenopausal osteoporosis, but mechanistic studies of this phenomenon are still focusing on molecular and genetic researches in model animal. Osteoporosis with iron accumulation is a distinct endocrine disease with complicated pathogenesis regulated by several proteins. However, the comprehensive proteome-wide analysis of human bone is lacking. Using multiplex quantitative tandem mass tag-based proteomics, we detected 2900 and quantified 1150 proteins from bone of 10 postmenopausal patients undergoing hip replacement. Comparing with non-osteoporosis patients, a total of 75 differentially expressed proteins were identified, comprising 53 downregulated proteins and 22 upregulated proteins. These proteins primarily affect oxidoreductase activity, GTPase activity, GTP binding, and neural nucleus development, were mainly enriched in neural, angiogenesis and energy-related pathways, and formed complex regulatory networks with strong interconnections. We ultimately identified 4 core proteins (GSTP1, LAMP2, COPB1, RAB5B) that were significantly differentially expressed in the bone of osteoporosis patients with iron accumulation, and validated the changed protein level in the serum of the medical examination population. Our systemic analysis uncovers molecular insights for revealing underlying mechanism and clinical therapeutics in osteoporosis with iron accumulation.